Fabrication of bioactive nanocomposites from chitosan, cress mucilage, and selenium nanoparticles with powerful antibacterial and anticancerous actions - El-Sherbiny, Mohsen M.; Orif, Mohamed I.; El-Hefnawy, Mohamed E.; Alhayyani, Sultan; Al-Goul, Soha T.; Elekhtiar, Rawan S.; Mahrous, Hoda; Tayel, Ahmed A. (Frontiers in Microbiology, 2023)
Natural bioactive alternatives are the utmost requests from researchers to provide biosafe and effectual health-guarding agents. The biopolymers chitosan nanoparticles (NCT), mucilage of cress seed (GCm; Lepidium sativum) and GCm-mediated selenium nanoparticles (GCm/SeNPs) was innovatively employed for fabricating novel bioactive natural nanocomposites (NCs) with elevated bioactivities as bactericidal (against Salmonella typhimurium and Staphylococcus aureus) and anticancer (against CaCo-2 and HeLa cells). The SeNPs were successfully generated with GCm and different NCs formulations were fabricated from NCT:GCm/SeNPs amalgam ratios included T1, T2 and T3 with 2:1, 1:1 and 1:2 ratios, respectively. The infrared analysis of synthesized molecules appointed apparent physical interactions among interacted molecules. The average particles' sizes and charges of molecules/NCs were (12.7, 316.4, 252.8 and 127.3 nm) and (-6.9, +38.7, +26.2 and -25.8 mV) for SeNPs, T1, T2 and T3, respectively. The biocidal assessment of NCs indicated that T1 was the strongest antibacterial formulation, whereas T3 was the superior anticancer amalgam. These NCs formulations could exceeded the biocidal potentialities of standard biocides.T1-NC could cause severe destructions/deformations in challenged S. typhimurium within 9 h, whereas T3-NCs induced apparent fluorescent apoptosis signs in treated HeLa cells. The prospective applications innovatively designed biocidal natural NCs are recommended for controlling pathogenic bacteria and fighting cancerous cells.